Peanut butter before the store - Bernard, Jan.; McGeehan, Dan (Mankato, MN : Child's World, 2012)
Explains how peanut butter is made, focusing on where the peanuts are grown, how they are processed and packaged, and how it becomes available to the consumer.
Yummy peanut butter -- A special kind of peanut -- On the peanut farm -- Shelling the peanuts -- A peanut butter factory -- Grinding and mixing -- Into the jars -- Onto your sandwich.
Includes bibliographical references (p. 32) and index.
3.8
K-3
Keywords: Peanut butter -- Juvenile literature; Peanut industry -- Juvenile literature; Peanut butter; Peanut industry; Peanut butter; Peanut industry